PELATIHAN OPTIMALISASI MICROSOFT OFFICE UNTUK MENINGKATKAN KEGIATAN MAHASISWA/i PADA PENGABDIAN MASYARAKAT DI UNIVERSITAS MAHAKARYA ASIA BATURAJA - Wisnumurti Wisnumurti; Sri Tita Faulina Faulina; Satria Novari (Universitas Majalengka, 2023)
Microsoft Office Optimization Training is one of the needs for technology in the office sector. Microsoft office is an office application package software made by Microsoft and designed to run under the Microsoft Windows and Mac OS X operating systems. The Microsoft Office training provided is Excel, Word and PowerPoint. The purpose of this Community Service activity is to improve student abilities in developing office applications. The method used with this activity is Lectures and practicum. This training is attended by students who will carry out Community Service activities in offices and agencies consisting of 20 people. This Microsoft Office training is a means of job training for female students in increasing understanding and skills in the skills area. The results of this training are expected to help female students in community service activities by providing initial experience to form identity and develop office skills and be able to socialize to the public in the world of work.